Measurement Properties of Wii Fit Free Jogging Virtual Distance - Gormley, John; Hussey, Juliette; Forde, Cuisle (My University, 2014)
Objective: The aim of this study was to examine the measurement properties of an outcome associated with the Nintendo(®) (Kyoto, Japan) game "Wii™ Fit Free Jogging" called virtual distance. Investigations into virtual distance were carried out with a view towards using this outcome measure as a tool to estimate fitness as part of a self-paced field-based exercise test. Materials and methods: Virtual distance achieved was recorded while participants jogged on a treadmill and stepped up and down a standardized step and while the game controllers (Wii remotes) were attached to electrically powered pedals moving at steady rates. Virtual distance was recorded at different time points and different speeds, using different consoles, using different Wii remotes, and using different virtual characters. Results: When movement of the Wii remote was kept constant, there was no significant difference in virtual distance reached at different times, with different consoles, with different Wii remotes, or with different virtual characters (P<0.05). There was a significant difference between virtual distances reached when the speed of movement of the Wii remote was changed. An increase in the speed of jogging on the spot, an increase in the rate of stepping per minute, and an increase in rotations per minute on automated pedals all resulted in increased virtual distance. At a constant speed, the rate of increase in virtual distance with time was consistent. Conclusions: Virtual distance appears to be a reliable measure that is sensitive to changes in the speed of movement of Wii remotes.
PUBLISHED
Keywords: Next Generation Medical Devices; Biomedical sciences